2020
DOI: 10.4236/ce.2020.1110156
|View full text |Cite
|
Sign up to set email alerts
|

Kazan State Medical University Survey after the Use of CyberPatient<sup>TM</sup> during COVID-19

Abstract: The COVID-19 pandemic created challenges for medical education, particularly for the acquisition of clinical skills. At Kazan State Medical University (KSMU), we used an online simulation platform called CyberPatient TM (CP) to provide a clinical environment in a virtual space with a variety of patients for students to practice their clinical skills. In this study, we surveyed 59 students who used CP in the 2020 spring semester. This survey's objectives were to gather the students' opinion on usability, value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…A separate survey study showed that 96% of students believed the CyberPatient platform was intuitive. In addition, over 90% of students considered CyberPatient a valuable teaching tool, and 89.9% perceived the CyberPatient platform to impact their clinical performance positively (Mukharyamova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A separate survey study showed that 96% of students believed the CyberPatient platform was intuitive. In addition, over 90% of students considered CyberPatient a valuable teaching tool, and 89.9% perceived the CyberPatient platform to impact their clinical performance positively (Mukharyamova et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Students did not indicate whether they had access to paid resources that gather not only the most interesting lectures, and videos, but also interactive simulators. The experience of Kazan Medical University in the use of the Cyberpatient platform showed that student satisfaction and motivation increase with the use of virtual simulators 12 . The results of the correlation analysis within the present study are concordant with the ndings obtained previously, con rming our assumption that the insu cient use of MOOCs and simulators has partially determined the poor VAS scores.…”
Section: Discussionmentioning
confidence: 99%